Photometry and Spectroscopy of SN 2024pxl: A Luminosity Link among Type Iax Supernovae - Singh, Mridweeka; Kwok, Lindsey A.; Jha, Saurabh W.; Dastidar, R.; Larison, Conor; Filippenko, Alexei V.; Andrews, Jennifer E.; Andrews, Moira; Anupama, G. C.; Arunachalam, Prasiddha; Auchettl, Katie; Banhidi, Dominik; et al. (Institute of Physics Publishing, 2026)
We present extensive ultraviolet to optical photometric and optical to near-infrared (NIR) spectroscopic follow-up observations of the nearby intermediate-luminosity (MV = −16.81 ± 0.19 mag) Type Iax supernovae (SNe Iax) 2024pxl in NGC 6384. SN 2024pxl exhibits a faster light curve than the high-luminosity members of this class, and slower than low-luminosity events. The observationally well-constrained rise time of ∼11 days and an estimated synthesized 56Ni mass of 0.03 M⊙, based on analytical modeling of the integrated spectral energy distribution light curve, are consistent with models of the weak deflagration of a carbon-oxygen white dwarf. Our optical spectral sequence of SN 2024pxl shows weak Si ii lines and spectral evolution similar to other high-luminosity SNe Iax, but also a prominent early-time C ii line, like lower-luminosity SNe Iax. The late-time optical spectrum of SN 2024pxl closely matches that of SN 2014dt, and its NIR spectral evolution aligns with that of other well-studied, high-luminosity SNe Iax. The spectral-line expansion velocities of SN 2024pxl are at the lower end of the SNe Iax velocity distribution, and the velocity distribution of iron-group elements compared to intermediate-mass elements suggests that the ejecta are mixed on large scales, as expected in pure deflagration models. SN 2024pxl exhibits characteristics intermediate between those of high-luminosity and low-luminosity SNe Iax, further establishing a link across this diverse class.